2022
DOI: 10.3390/biology11081175
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Upper Limb Isometric Task in Perceived and Performance Fatigability of Elderly Subjects: A Quasi-Experimental Study

Abstract: Isometric activity can be used as a strategy to improve health, fitness, and functional performance in the elderly population, but differences in fatigability may occur. This study aimed to understand fatigability behavior during an upper limb isometric task (ULIT) and the role of health status and physical activity in the fatigability of elderly participants. Thirty-two (32) elderly participants (72.5 ± 5.18 years) were instructed to perform ULIT. The Borg CR10 scale and task failure point (TTF) were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Our previous research showed a positive relationship between perceived and performance fatigability in the final stage of the activity differences and significant changes in mA, which revealed the presence of upper limb motion in the sagittal plane and an overall increase in movement variability, with sex-related differences 20,21 . This study aimed to examine the relationship between PcFat and upper limb kinematic behavior during a ULPSIT.…”
Section: Discussionmentioning
confidence: 89%
“…Our previous research showed a positive relationship between perceived and performance fatigability in the final stage of the activity differences and significant changes in mA, which revealed the presence of upper limb motion in the sagittal plane and an overall increase in movement variability, with sex-related differences 20,21 . This study aimed to examine the relationship between PcFat and upper limb kinematic behavior during a ULPSIT.…”
Section: Discussionmentioning
confidence: 89%
“…Our findings were not in accordance with the evidence from previous research that has shown that usually, men were more fatigable than women when performing isometric contractions at low to moderate intensities [56][57][58][59] and that older subjects were less fatigable than young subjects for upper-and lower-limb muscles for an isometric-contraction fatiguing task at the same relative intensity [52,60]. However, it is well known that these discrepancies are task specific [57,61], rely on the details and demands of the task [17], and are associated with anatomical, biomechanical, and physiological factors [17,42,56,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…First, the randomization sampling procedure should be carried out with a greater sample to reduce sample bias and clarify some of the results obtained. Second, since TTF is dependent on the will of the participants to maintain (or not) the task, and is related to perceived fatigability [14,42], TTF may be underestimated for some participants. So, in future studies, it would be important to add other performance and perceived fatigability outcomes to check the perceptual influence on performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigability is associated with decreased exercise tolerance and adherence [7]. Additionally, the ability to perform repetitive or prolonged daily physical activities, particularly walking, climbing stairs, and carrying loads, is limited by fatigability [8].…”
Section: Introductionmentioning
confidence: 99%